Studi Analisis “Brian Tracy” dan “ Struzel” Seni Memotivasi Diri untuk Mengubah Mimpi Menjadi Takdir - Adelia Adelia (Journal of Society Counseling, 2023)
This research examines "Brian Tracy's" and "Dan Strutzel's" Thought Analysis Studies in The Art of Self-Motivating Strategies for Turning Dreams into Destiny. The purpose of this study was to find out the concept of self-motivating art according to "Brian Tracy" & " Strutzel" turning dreams into destiny, the concept of turning dreams into destiny according to Islam, and the differences between western motivational concepts and Islamic motivational concepts. Liberary research research methodology, with data collection techniques including editing, data tagging and systematizing. The results of the research are first, in the books "Brian Tracy" and "Dan Strutzel" explaining that a person has the right to succeed but achieving success requires great determination and high motivation, prioritizing stable mental achievement in someone who wants to be motivated to develop. Second, turning dreams into destiny according to Islamic view, namely dreams that can become destiny can be realized with sincerity, greatness of mind, reason of one's soul to make it happen must try hard, pray and put your trust. Third, the western concept of motivation as a motivational process in terms of the intensity and persistence of an individual to achieve the goals he expects. While the concept of motivation according to Islam is to realize the welfare of all humans, under the protection of religion (ad-dien), soul (nafs), reason (aql), descent (nasbh). Fulfillment of these human needs with dharuriyat needs, is urgent and must be fulfilled because it contains falah and life thayyibah which means motivation arises in humans based on the guidance of Rasulullah SAW. Key words: Self Motivation, Destiny, Dreams